The Influence of Leadership and Training on the Performance of Hajj Officers with Work Motivation as a Mediating Variable: A Study on the Hajj Implementation at Jakarta Pondok Gede Embarkation - Syakiroh, Syakiroh; Wahono, Puji; Wiradendi Wolor, Christian (International Journal of Economics, Management and Accounting (IJEMA), 2025)
The performance of Hajj officers is crucial in ensuring the smooth and effective organization of the Hajj pilgrimage, a responsibility that is influenced by various factors such as leadership, training, and work motivation. This study aims to analyze the effects of leadership and training on the performance of Hajj officers, with work motivation serving as a mediating variable. The research was conducted on the officers responsible for organizing the Hajj pilgrimage at the Jakarta Pondok Gede Embarkation, a major center for Hajj operations in Indonesia. A quantitative approach was used, with data collected via surveys distributed to a sample of 100 Hajj officers. The data were analyzed using structural equation modeling (SEM) to test the direct and indirect effects of leadership and training on officer performance, with work motivation as a mediator. The findings indicate that both leadership and training significantly influence the performance of Hajj officers, with work motivation playing a crucial role in mediating these relationships. Effective leadership enhances officers' motivation, which in turn improves their performance, while comprehensive training programs equip officers with the skills necessary for optimal performance. This study underscores the importance of leadership, training, and motivation in improving the overall performance of Hajj officers, which ultimately contributes to the success of Hajj operations. These findings have practical implications for enhancing the management and organization of Hajj pilgrimages, particularly in Indonesia.